Chinese Historical BL by Thai Writers: The Thai BL Polysystem in the Age of Media Convergence. - Jooyin Saejang (Intersections: Gender & Sexuality in Asia & the Pacific, 2023)
Conclusion By investigating the availability of Chinese BL novels and audiovisual productions in Thailand as well as interviews with eight Thai authors of Chinese historical BL, in this paper I have shed light on how such Chinese BL imports have driven Thailand's domestic BL economy and, more importantly, contributed to the birth of a new BL subgenre, that is, Chinese historical BL by Thai authors. Meanwhile, Chinese historical BL by Thai authors makes up about 15-20 percent of all BL publications in the Thai market. It is noteworthy that despite the relatively low number of published Thai authors of Chinese historical BL, the import of Chinese BL has greatly enriched the domestic BL scene. Since the mid-2010s, a genre of once underground novels and audiovisual productions known in English as Boys' Love, or BL for short, has been catapulted to the centre of popular culture in East and Southeast Asia.